Spatial Characteristics and Genesis of Tight Clastic Reservoirs in Yingcheng Formation of Changling Fault Depression in the Southern Songliao Basin. (29th September 2022) - Mu, Hansheng; Li, Ruilei; Zhu, Jianfeng; Xu, Wen; Qu, Xiyu
Abstract : Tight oil and gas has become a hot spot for unconventional oil and gas exploration. How to find high-quality reservoirs under the conditions of low porosity and permeability has become a key issue restricting tight oil and gas exploration. This paper takes the deep-seated tight clastic rocks in the Changling fault depression in the Songliao Basin as the research object and comprehensively applies various technologies and methods such as microscopic observation, temperature measurement of inclusions and paleopressure recovery, and water-rock simulation experiments, to summarize the storage of tight reservoirs. Set space types and analyze their formation mechanism. The research results show that (1) the tight clastic reservoir space types of Yingcheng Formation in the Longfengshan subsag of the Changling fault depression in the southern Songliao Basin include residual primary pores, secondary dissolved pores, and microfractures, with mainly secondary dissolved pores; (2) pore lining chlorite is an important mechanism for the preservation of primary pores; (3) water-rock simulation experiments have confirmed that volcanic rock cuttings are easy to dissolve and are the main contributor to the secondary dissolution pores in the study area; and (4) the Raman displacement technique of methane inclusions has confirmed the existence of overpressure, which is the cause of hydrocarbon generation and pressurization and is the main motivation for a microcrack formation.